The influence of group decision making on indecisiveness-related decisional confidence - Andrea L. Patalano; Zachary LeClair (Judgment and Decision Making, 2011)
Indecisiveness is an individual difference measure of chronic difficulty and delay in decision making. Indecisiveness is associated with low decisional confidence and distinct patterns of pre-choice information search behavior. The present study explored whether the confidence levels and search behaviors associated with individual indecisiveness also emerge in group decision making contexts. In this study, 97 decisive and indecisive participants were assigned to make a decision individually or in a homogenous three-person group. Indecisiveness score was found to predict participant decisional confidence in the individual condition but not in the group condition, with group participants being overall more confident than individuals. Similar results were obtained for other related measures of participants’ perceptions of the decision task. Surprisingly, no indecisiveness-related differences in information search were found, suggesting that other aspects of the group process contribute to increased confidence. The results provide initial evidence that indecisiveness does not influence group decision making and that, especially for indecisive individuals, working in groups may be a way to boost decisional confidence.